A literature review about cardiovascular risk in patients with kidney disease - S. Alvarez, Cristian J.; Jorge A. D. Cancino; Karen A. Z. Ramírez (International Journal Of Community Medicine And Public Health, 2023)
More than 700 million individuals are thought to have chronic kidney disease (CKD) globally, and the incidence is continuing to rise as a result of an aging population and the spread of chronic illnesses like diabetes and hypertension. The most common cause of morbidity and death in nephropathy patients is cardiovascular disease. In clinical practice, managing nephropathy and cardiovascular risk in nephropathic patients is a significant problem. Each patient needs a thorough examination and specialized treatment. To lower the risk of cardiovascular events in nephropathy patients, cardiovascular risk factors must be prevented and promptly treated. To increase the quality of life and survival of nephropathic patients, it is crucial to recognize and treat cardiovascular problems.